The correlation between structural attributes and magnetic shielding of some metal nanoparticles engineered polymeric surfaces. (2022) - Vrinceanu, Narcisa; Coman, Diana
Abstract: Polymeric structures for use in magnetic environments are of great importance for applications ranging from simple magnetic barriers to the design of high dimensions devices, or vehicles. The damage caused by magnetic radiations is invisible, slow, and accumulative. This can lead to genetic damage, reproductive defects, cancer, neurological degeneration and nervous system dysfunction. This research work has focused on the effects of magnetic radiations onto some polymeric supports coated with different molar ratios of Zn/Al oxides and their response to magnetic radiations. Of particular interest here was the adapting the coating conditions with the magnetic barrier of the coated polymeric supports. The engineered polymeric supports have been characterized using X-ray diffraction, UV–VIS spectroscopy, SEM techniques, and magnetic measurements. The XRD and SEM results are well correlated revealing the clustering of the Zn 2+ cations and the forming of ZnO nanoparticles onto the surface of the polymeric support for all used cationic ratios. The magnetic measurements proved an average magnetic nature in ZnO/AlO NPs deposited onto polymeric supports.